Increased matriptase zymogen activation by UV irradiation protects keratinocyte from cell death. Issue 1 (July 2016) - Chen, Chi-Yung; Chen, Cheng-Jueng; Lai, Chih-Hsin; Wu, Bai-Yao; Lee, Shiao-Pieng; Johnson, Michael D.; Lin, Chen-Yong; Wang, Jehng-Kang
Highlights: We investigate the role of matriptase in keratinocyte exposed to UV irradiation. Human skin matriptase activation is induced in respond to acute UV irradiation. ROS generation is likely involved in UV-triggered matriptase zymogen activation. Matriptase protects keratinocytes from apoptosis induced by acute UV exposure. Matriptase activity also significantly increases in chronically solar damaged skin. Abstract: Background: Overexposure to ultraviolet (UV) derived from solar light causes skin damage by causing DNA lesions and the generation of reactive oxygen species (ROS) in keratinocytes and other epidermal cells. The type 2 transmembrane serine protease matriptase has characteristics that allow keratinocytes to respond to/recover from, environmental insults to the skin. This response may depend on its roles in epidermal proliferation and early differentiation, and its rapid activation in response to changes in the cellular chemical milieu, including increased oxidative stress. Objective: We investigate the regulation of matriptase activation and its role in the response of the skin to exposure to different parts of the UV spectrum including UVA UVB, and UVR. Methods: The activation state and distribution of matriptase in ex vivo UV exposed human skin specimens and sun damaged skin samples were analyzed by immunohistochemistry. HaCaT immortalized human keratinocytes were also used to investigate the mechanism of matriptase zymogen activation induced by UV irradiation. Levels of cytosolic ROS were determined by H2 DCF assay. Activated matriptase, PARP and caspase 3 cleavage was analyzed by Western blotting, and the apoptotic ratio was measured by Hoechst 33258 staining. Results: UVB exposure rapidly increased matriptase zymogen activation in the basal keratinocytes of skin samples. Activated matriptase was also detected at much higher levels in both the basal and spinous layer keratinocytes in sun damaged skin with actinic elastosis. UVB and solar light-induced matriptase zymogen activation likely results from UV-induced ROS generation, given that UVR, UVA, and UVB irradiation induced HaCaT human keratinocytes to activate matriptase in a dose- and time-dependent manner, and that this was suppressed by the ROS scavenger N - tert -butyl-α-phenylnitrone and reducing agent dithiothreitol. Matriptase deficient HaCaT keratinocytes were more susceptible to UV-induced apoptosis than control cells, suggesting a protective role for matriptase in UV exposed keratinocytes. Conclusion: UV irradiation/ROS induced matriptase proteolysis may have short term protective effects and contribute to the recovery from acute epidermal damage and/or pathology of skin with chronic sun damage.